2020
DOI: 10.1002/adma.202000004
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Self‐Powered Photodetector Arrays Based on All‐Inorganic CsPbBr3 Quantum Dots

Abstract: high-performance photodetection is highly desirable in various fields, including optical communication, imaging, and environmental monitoring. [4][5][6] Currently, GaN, Si, InGaAs, and other semiconductors have dominated the ultraviolet to near-infrared photodetection market. [7][8][9][10] These detectors are mostly assembled on rigid substrates and usually require relatively thick active materials for photonic detection, therefore, they are not compatible with flexible systems or suitable for low cost manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 59 publications
0
99
0
Order By: Relevance
“…S2d). On the other hand, PQDs have been widely utilized to fabricate optoelectronic devices including photosensors [33], photomemories [34] and photo-sensory neurons [8] because of their excellent photosensitivity. In our case, the introduction of CsPbBr 3 PQDs is expected to provide the devices with photosensitivity, so that light can be used as another control signal to adjust the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…S2d). On the other hand, PQDs have been widely utilized to fabricate optoelectronic devices including photosensors [33], photomemories [34] and photo-sensory neurons [8] because of their excellent photosensitivity. In our case, the introduction of CsPbBr 3 PQDs is expected to provide the devices with photosensitivity, so that light can be used as another control signal to adjust the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…As the incident power density increased, the photocurrent became larger accordingly, due to that more photoinduced carriers were produced and collected. The power-dependent photocurrent can be fitted by the power law (I ph ∝ P β ), where β is the exponent [54]. β was determined as 0.88, as shown in Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…Also, Shen et al reported all‐inorganic cesium lead bromide (CsPbBr 3 ) QD‐based photodetectors with reduced defect densities, exhibiting an enhanced photo‐responsivity of 10.1 A W −1 , a specific detectivity of 9.35 × 10 13 Jones, and a current on/off ratio up to 10 4 . [ 161 ] In particular, the cesium bromide (CsBr)/potassium bromide (KBr) treatment improved the surface morphology and the crystallinity of the film, resulting in enhanced charge transfer efficiency and lower leakage current.…”
Section: Qd‐based Photonic Devicesmentioning
confidence: 99%
“…In addition, flexible photodetector based on perovskite CsPbI 3 QDs with the CsBr/KBr treatment was also presented by Shen et al (Figure 12e,f). [ 161 ] The photo‐induced current retained more than 93% of original value after 60° bending and 1600 bending cycles. With high tensile strength and good stability, the flexible photodetectors ensured appropriate toughness for high photonic response and gain with great robustness against repetitive bending and stretching condition.…”
Section: Applicationsmentioning
confidence: 99%